2010
DOI: 10.1111/j.1365-2036.2010.04379.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐arterial therapy with cisplatin suspension in lipiodol and 5‐fluorouracil for hepatocellular carcinoma with portal vein tumour thrombosis

Abstract: SUMMARY BackgroundPortal vein tumour thrombosis is a negative prognostic factor for hepatocellular carcinoma (HCC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 35 publications
0
44
0
Order By: Relevance
“…Furthermore, Park et al [9] showed in a study of 41 patients with unresectable HCC that repeated HAIC with high-dose 5-FU (500 mg/m 2 , days 1–3) and cisplatin (60 mg/m 2 , day 2) for 3 days significantly improved survival in patients who responded to the treatment. In this study, we selected HAIC as the method of adjuvant therapy after curative liver resection because there is growing evidence that some agents such as 5-FU and cisplatin show anticancer effects in advanced HCC when delivered into the hepatic artery [18,19,20]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Park et al [9] showed in a study of 41 patients with unresectable HCC that repeated HAIC with high-dose 5-FU (500 mg/m 2 , days 1–3) and cisplatin (60 mg/m 2 , day 2) for 3 days significantly improved survival in patients who responded to the treatment. In this study, we selected HAIC as the method of adjuvant therapy after curative liver resection because there is growing evidence that some agents such as 5-FU and cisplatin show anticancer effects in advanced HCC when delivered into the hepatic artery [18,19,20]. …”
Section: Discussionmentioning
confidence: 99%
“…Other Regimens Nagamatsu et al [29] assessed the efficacy of cisplatin (DDP-H) in a lipiodol emulsion combined with 5-FU in patients (n=51) with HCC and PVTT. The RR was 86.3%, the MST was 33 months, treatment was well tolerated, and severe toxicity was infrequent (only one case of grade 3 toxicity [thrombocytopenia]).…”
Section: -Fu Arterial Infusion and Interferon Therapy (Fait)mentioning
confidence: 99%
“…For patients with portal vein tumor thrombosis, HAIC using low-dose cisplatin and 5-fluorouracil (5-FU) achieved a response rate of 48% (12) and a cisplatin-Lipiodol emulsion and 5-FU achieved a response rate of 86.3% (13). Although these two retrospective regimens achieved high response rates, they require catheter placement and a continuous infusion of anticancer agents.…”
Section: Introductionmentioning
confidence: 99%